ANALISIS KESULITAN BELAJAR SISWA KELAS III DALAM PEMBELAJARAN TEMATIK INTEGRATIF DI SEKOLAH DASAR - Alifia Rahmah Burhanudin; Hadi Rohyana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to identify and analyze learning difficulties experienced by class III students in integrative thematic learning at Wadas IV State Elementary School. The research method used is qualitative with a case study approach. Data was collected through observation, interviews and questionnaires given to students and teachers. The research results show that students' learning difficulties include understanding concepts, reading and writing skills, and learning motivation. Factors causing these difficulties include a lack of interesting learning media, less varied teaching methods, and limited home learning support. The recommendations given include developing more interactive learning media, increasing teacher competence in managing integrative thematic classes, and increasing collaboration between schools and parents to support students' learning processes at home. It is hoped that these findings can contribute to the development of more effective learning strategies in overcoming students' learning difficulties at the basic education level. There are two factors that cause students to experience learning difficulties: internal and external factors. For example, students' lack of attention to subject matter, lack of student participation and response when participating in teaching and learning activities, students' slow understanding of the material, unsatisfactory test scores, the influence of peers who always play with students, the influence of friends around where they live.